Art 21 art in the twenty-first century. Seasons one and two (Distributed by PBS Home Video, 2003)
Meet diverse contemporary artists through revealing profiles that take viewers behind the scenes into artist' studios, homes, and communities to provide an intimate view of their lives, work, sources of insipiration and creative processes.